TECHNOLOGY FOR IMPROVING MECHANISMS OF CREATIVE TEACHER PERSONALITY FORMATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In this article, the mechanisms of forming a creative teacher's personality, Pedagogical personnel should work in accordance with the requirements of the times, have deep knowledge, skills, skills and culture to educate a well-developed person in all aspects, creativity of the teacher, the latest innovations in his field, thus in addition, detailed information is given about being aware of events and happenings in the whole society, and being able to use innovative news appropriately in their activities.